Post-earthquake evaluation of damage and residual performance of UHPSFRC piers based on nonlinear model updating. (26th May 2019) - He, Li-Xiang; Wu, Chengqing; Li, Jianchun
Abstract: This paper presents an innovative approach for damage and residual performance evaluation of ultra-high performance steel fiber reinforced concrete (UHPSFRC) piers after earthquakes utilizing low-level vibration tests. A nonlinear fiber section element model is constructed in OpenSees to simulate the hysteretic behavior of a UHPSFRC bridge pier. Experimental data from a UHPSFRC column is utilized to verify the accuracy of the nonlinear numerical model. Based on the nonlinear fiber section element model, a new technique of nonlinear finite element model updating involving two updating stages is developed. This new method is designed to incorporate the maximum and minimum strains of section fibers as the updating parameters. By forming the objective function from the modal information, the damage parameters related to the nonlinear material model can be updated by solving the constrained optimization problem. To validate the efficiency of this updating approach, it has been applied to a numerically simulated UHPSFRC pier. With using the updated nonlinear finite element model, the residual axial loading capacity and post-seismic performance of the UHPSFRC pier are examined. The numerical results indicate that the updated nonlinear finite element model can be used not only to assess the current damage state of the UHPSFRC pier but also to predict its future performance after an earthquake. Finally, the noise effect on the proposed method is also investigated. The results reveal that the post-earthquake evaluation approach for UHPSFRC piers based on this study's updating algorithm is robust to noise. Highlights: A damage detection and residual performance evaluation method for UHPSFRC piers after earthquakes is proposed. A two-stage nonlinear model updating method is developed using low-level vibration data. The updated nonlinear finite element model is adopted to predict the remaining performance of the damaged UHPSFRC piers. The proposed post-earthquake evaluation approach is robust to noise.